"*.vg *-pl.info" 修訂間的差異

出自 DDCC TCAD TOOL Manual
前往: 導覽搜尋
 
(未顯示同一使用者於中間所作的 19 次修訂)
行 11: 行 11:
 
end
 
end
   
The PL can be calculated by
 
 
For n=1,C_e_N
 
for m=1,V_HH_M
 
for Ei=0, Emax
 
<math> E=Ei * dE </math>
 
<math> fe = \frac{1}{1+exp(\frac{E-Efn}{k_BT})} </math>
 
<math> fh = \frac{1}{1+exp(\frac{Efp-E}{k_BT})} </math>
 
<math> Rsp(Ei) = Rsp(Ei) + dE * Ei * |\langle\phi_e(n) |\phi_hh(m) \rangle |^2 * fe * fh* \frac{1}{\sqrt(2*\pi) \sigma} exp( -{(Ek-Ei)^2}{2*\sigma^2}) </math>
 
 
   
end
 
 
The PL of e to HH can be calculated by
end
 
  +
Rsp=0.0
end
 
  +
<math> const = \frac{1}{3} \frac{e_{0}^{2} * n_{r}}{2\pi\epsilon_{0}*m_{0}*c^3\hbar^2} * Ep </math>
  +
<math> N_{2D} = \frac{ m_r^* }{\pi\hbar^2} </math>
  +
<math>For~~ n=1,~C_{e,n} </math>
  +
<math>for~~ m=1,V_{HH,m} </math>
  +
<math>for~~ E_{\hbar\omega}=0,~~ Emax </math>
  +
<math>for~~ Ek = Ei - 5\sigma~~ ,~~ Ei+5\sigma </math>
  +
<math> If Ek > E_{n,e}-E_{hh,m} =E_{g,eff} then </math>
  +
<math> Ee = E_{e,n} +(Ek-E_{g,eff}) * \frac{m_r^{*}}{m_{e}^{*}} </math>
  +
<math> Ehh = E_{hh,m}-(Ek-E_{g,eff}) * \frac{m_r^{*}}{m_{hh}^{*}} </math>
 
<math> fe = \frac{1}{1+exp(\frac{Ee-Efn}{k_BT})} </math>
 
<math> fh = \frac{1}{1+exp(\frac{Efp-Ehh}{k_BT})} </math>
 
<math> Rsp(Ei) = Rsp(Ei) + const*dE * Ei * |\langle\phi_{e,n} |\phi_{hh,m} \rangle |^2 * fe * fh* \frac{1}{\sqrt{2\pi} \sigma} exp( -\frac{(Ek-Ei)^2}{2*\sigma^2}) * N_{2D} </math>
 
<math>end ~if</math>
 
<math>end</math>
 
<math>end </math>
  +
<math>end </math>
  +
<math>end</math>
  +
  +
  +
The PL of e to LH can be calculated by
  +
Rsp=0.0
  +
<math>For~~ n=1,~C_{e,n} </math>
  +
<math>for~~ m=1,V_{LH,m} </math>
  +
<math>for~~ E_{\hbar\omega}=0,~~ Emax </math>
  +
<math>for~~ Ek = Ei - 5\sigma~~ ,~~ Ei+5\sigma </math>
  +
<math> If Ek > E_{g,eff} = E_{n,e}-E_{lh,m} </math>
  +
<math> Ee = E_{e,n} +(Ek-E_{g,eff}) * \frac{m_r^{*}}{m_{e}^{*}} </math>
  +
<math> Elh = E_{lh,m}-(Ek-E_{g,eff}) * \frac{m_r^{*}}{m_{lh}^{*}} </math>
  +
<math> fe = \frac{1}{1+exp(\frac{Ee-Efn}{k_BT})} </math>
  +
<math> fh = \frac{1}{1+exp(\frac{Efp-Elh}{k_BT})} </math>
  +
<math> Rsp(Ei) = Rsp(Ei) + const*dE * Ei * |\langle\phi_{e,n} |\phi_{lh,m} \rangle |^2 * fe * fh* \frac{1}{\sqrt{2\pi} \sigma} exp( -\frac{(Ek-Ei)^2}{2*\sigma^2}) * N_{2D} </math>
  +
<math>end ~~if</math>
  +
<math>end</math>
  +
<math>end </math>
  +
<math>end </math>
  +
<math>end</math>

於 2025年1月28日 (二) 16:27 的最新修訂

C_e_N, V_HH_M, V_LH_L, nr , Epp
For n=1,C_e_N
  for m=1,V_HH_M
     C_{n},~ V_{hh,m}, ~|\langle \phi_{e,n},\phi_{hh,m}\rangle |^{2},~ E_{n,e}-E_{hh,m},~ E_{e,n},~E_{fn},~E_{fp},~m_{e},~m_hh, N_{2D,DOS,r} 
  end 
end
For n=1,C_e_N
  for m=1,V_LH_L
     C_{n},~ V_{lh,m}, ~|\langle \phi_{e,n},\phi_{lh,m}\rangle |^{2},~ E_{n,e}-E_{lh,m},~ E_{e,n},~E_{fn},~E_{fp},~m_{e},~m_lh, N_{2D,DOS,r} 
  end 
end


The PL of e to HH can be calculated by

Rsp=0.0 
 const = \frac{1}{3} \frac{e_{0}^{2} * n_{r}}{2\pi\epsilon_{0}*m_{0}*c^3\hbar^2} * Ep   
 N_{2D} = \frac{ m_r^* }{\pi\hbar^2} 
For~~ n=1,~C_{e,n} 
  for~~ m=1,V_{HH,m} 
     for~~ E_{\hbar\omega}=0,~~ Emax   
         for~~ Ek = Ei - 5\sigma~~ ,~~ Ei+5\sigma   
             If Ek >  E_{n,e}-E_{hh,m} =E_{g,eff} then      
                Ee =  E_{e,n} +(Ek-E_{g,eff}) * \frac{m_r^{*}}{m_{e}^{*}}  
                Ehh = E_{hh,m}-(Ek-E_{g,eff}) * \frac{m_r^{*}}{m_{hh}^{*}}          
                fe = \frac{1}{1+exp(\frac{Ee-Efn}{k_BT})} 
                fh = \frac{1}{1+exp(\frac{Efp-Ehh}{k_BT})} 
                Rsp(Ei) = Rsp(Ei) + const*dE * Ei * |\langle\phi_{e,n} |\phi_{hh,m} \rangle |^2 * fe * fh* \frac{1}{\sqrt{2\pi} \sigma} exp( -\frac{(Ek-Ei)^2}{2*\sigma^2}) * N_{2D} 
            end ~if
         end
     end 
  end 
end


The PL of e to LH can be calculated by

Rsp=0.0 
For~~ n=1,~C_{e,n} 
  for~~ m=1,V_{LH,m} 
     for~~ E_{\hbar\omega}=0,~~ Emax   
         for~~ Ek = Ei - 5\sigma~~ ,~~ Ei+5\sigma   
             If Ek >  E_{g,eff} = E_{n,e}-E_{lh,m}       
                Ee =  E_{e,n} +(Ek-E_{g,eff}) * \frac{m_r^{*}}{m_{e}^{*}}  
                Elh = E_{lh,m}-(Ek-E_{g,eff}) * \frac{m_r^{*}}{m_{lh}^{*}}          
                fe = \frac{1}{1+exp(\frac{Ee-Efn}{k_BT})} 
                fh = \frac{1}{1+exp(\frac{Efp-Elh}{k_BT})} 
                Rsp(Ei) = Rsp(Ei) + const*dE * Ei * |\langle\phi_{e,n} |\phi_{lh,m} \rangle |^2 * fe * fh* \frac{1}{\sqrt{2\pi} \sigma} exp( -\frac{(Ek-Ei)^2}{2*\sigma^2}) * N_{2D} 
            end ~~if
         end
     end 
  end 
end